PERAN KOLABORATIF PEMERINTAH DAN LEMBAGA PENDIDIKAN DALAM MENCEGAH PERNIKAHAN DINI DI WILAYAH PERKOTAAN - Dinanti, Dara; Sary, Juwita Puspita; Nurilahi, Balqis; Sari, Refi Novita; Rahmat, Ronni Khairul; Yarmunida, Miti (CV. Kalimasada Group, 2025)
Early marriage in Pagar Dewa Village, Selebar District, Bengkulu City is still rampant and has long-term impacts ranging from hampered education, health risks, psychological pressure, to increased poverty and divorce, especially for girls. To overcome this problem, community service uses a Participatory Action Research (PAR) approach which involves counseling and guidance on early marriage prevention. Before the early marriage prevention service was carried out, only 31% of participants had knowledge about the impact of early marriage, but after the education series the number increased to 92%, showing a significant increase in understanding, the ability to make independent decisions, and the mastery of reproductive rights and life skills. These results confirm that an interdisciplinary approach that integrates aspects of health, education, religion, and psychosocial empowerment effectively provides sustainable solutions to prevent early marriage and improve the quality of the young generation in Bengkulu Province.